Cytotoxic T lymphocyte-Associated Antigen +49G Variant Confers Risk for Anti-CCP- and Rheumatoid Factor-Positive Type of Rheumatoid Arthritis Only in Combination with CT60∗G Allele. (27th August 2009) - Farago, Bernadett; Kisfali, Peter; Magyari, Lili; Polgar, Noemi; Melegh, Bela
Abstract : Controversial observations have been published on the association of the cytotoxic T lymphocyte associated antigen gene's variants with rheumatoid arthritis (RA). After genotyping 428 patients and 230 matched controls, the prevalence of theCT 60 ∗ G allele was more frequent in RF- and/or anti-CCP-seropositive RApatients, compared to the healthy controls (P < .001 ). Regression analysis revealed that theCT60 ∗ G allele is a possible predisposing factor for RA in these subgroups. No accumulation of the+ 49 ∗ G allele was found among patients, and this variant was not found to correlate with RA. Assaying the possible genotype variations, the+ 49 ∗ G-C T 60 ∗ G allelic combination was accumulated in seropositive RA-subtypes, and was associated with the risk of RA (OR = 1.73, P = .001 for the whole RA-population). Although the+ 49 ∗ G allele did not mean a predisposition to RA alone, in combination withC T 60 ∗ G it, also conferred risk, suggesting that the+ 49 A / G variant is associated with the risk of RA only in certain haplotypes.